2008
DOI: 10.1097/bcr.0b013e31817112f1
|View full text |Cite
|
Sign up to set email alerts
|

Self-Immolation in Iran

Abstract: Deliberate self-inflicted burn is rare in high-income countries, but is reported more frequently in low- and middle-income countries, especially in Asia and Africa. Rates in Iran are among the highest in the world, with up to 71% of committed suicides conducted via self-immolation in some regions. The objective of this study was to identify the epidemiologic features and factors of self-immolation in Iran to aid in development of effective intervention programs. In a review study, two national databases were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
92
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 8 publications
7
92
3
1
Order By: Relevance
“…To make matters even worse, it has been clearly shown that intentional burn patients have a larger mean total body surface area (TBSA) burned, a longer hospital stay, and a higher mortality compared to other burned patients [17]. In some series, mortality in these patients reaches an astounding 80% [3,18].…”
Section: Introductionmentioning
confidence: 99%
“…To make matters even worse, it has been clearly shown that intentional burn patients have a larger mean total body surface area (TBSA) burned, a longer hospital stay, and a higher mortality compared to other burned patients [17]. In some series, mortality in these patients reaches an astounding 80% [3,18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Iran showed that it is more prevalent among Kurdish population. Ilam and Kermanshah are the first two cities with highest frequency of completed self-immolation in Iran (2). Both cities are located Western of Iran and with high proportion of Kurdish people.…”
mentioning
confidence: 99%
“…Unfortunately in Iran burn is a widely common way of suicide (3). Around 30% of suicides are committed by burning (2). Suicidal behavior incidence was reported up to 19 per 100000 people in 2005 (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] The role of these factors in survival rate is not clear in people who have attempted suicide. Between all methods of suicide, self-immolation is more deleterious, painful, costly, and fatal, [14,15] and people who burn themselves are hardly treated. [12,16] This study is designed to assess the survival rate and affecting factors of survival in self-immolation attempters in one of the west provinces of Iran (Kermanshah) which has one of the highest rates of suicide and self-immolation.…”
mentioning
confidence: 99%